Death of a wicked witch - Hollis, Lee (Hollis, Lee. Hayley Powell food and cocktails mystery, 2020)
"Bar Harbor, Maine, is quieter in the off-season, but the population has just increased a bit with the arrival of Ted and Trudy Lancaster. Ted's taking over for a retiring minister, and Trudy runs a food truck called Wicked 'Wiches. When she stops in at the Island Times office to place an ad, Hayley happily devours the sample sub Trudy offers -- and the two become fast friends. When Trudy tragically dies in her truck while catering a Halloween party, suspicion falls on a cranky, competitive caterer who'd made veiled threats to Trudy. But the case becomes more complicated when Hayley's husband admits he'd seen someone dressed as a witch hurrying away from the food truck -- not very helpful when countless women at the party wore the same costume. Now Hayley finds herself sandwiched between witches and witnesses as she considers a smorgasbord of suspects. If she finds the killer, she'll be a local hero . . ."--Provided by publisher.